Polypyrrole nanoparticles for tunable, pH-sensitive and sustained drug release. Issue 21 (7th June 2015) - Samanta, Devleena; Meiser, Jana L.; Zare, Richard N.
<x xml:space="preserve">Abstract</x> Charged drug molecules from nanoparticles are released by changing the pH of the surroundings and fine-tuned by adding appropriate amphiphiles.